Evolution of naturally arising SARS-CoV-2 defective interfering particles - Samer Girgis; Zaikun Xu; Spyros Oikonomopoulos; Alla D. Fedorova; Egor P. Tchesnokov; Calvin J. Gordon; T. Martin Schmeing; Matthias Götte; Nahum Sonenberg; Pavel V. Baranov; Jiannis Ragoussis; Tom C. Hobman; et al. (Communications Biology, 2022)
Genomes from defective interfering (DI) particles following serial passaging of SARS-CoV-2 reveal a fusion protein that attenuates viral replication. Synthetic, recombinant DI genomes are designed to interfere with SARS-CoV-2 replication.